Behavioral Finance and "Black Swan" Theory - Brajković, Ana; Peša, Anita Radman (Oeconomica Jadertina, 2017)
The regular appearance of anomalies in the conventional economy contributed to creation and shaping of behavioral finance. These anomalies directly or indirectly threatened the modern financial and economic theory, based on rational behavior and rational decision-making. Behavioral finance represents a new approach to the field of finance, which takes into account psychological aspects of human and investor's life. Psychology defines certain concepts of behavior and prejudices that have contributed to the irrational and often harmful decision-making process. The focus of behavioral finance is on how individual investors make decisions, that is, how they interpret and react to specific information. The authors also present behavioral finance through the term of Black Swan defining it as an unpredictable event with serious consequences and when such event happens, people tend to give explanations to make it predictable and explainable. Event with The Black Swan label, for example, is the global financial crisis of 2008. The authors analyze and other modern financial theories and compare them with the standard financial theories to point out the need for further research in the field of financial theory.
Keywords: Financial theories; behavioral finance; Black Swan